The Impact of the Implementation of Regional Autonomy on the Village Government System: An Overview of Siyasah Syar’iyyah - Muhammad Syarif; Muhamad Aswin; Ali Imron (State Institute for Islamic Studies Palu, 2022)
This article describes the impact of implementing regional autonomy on the village government system in terms of Islamic law policies. The location of the research concentration is in Petimbe Village, Sigi Regency, Central Sulawesi Province. Empirical legal methods and qualitative approaches are used to holistically understand the phenomena experienced by the subjects, including behavior, motivation, and action. The implementation of regional autonomy in the village government system positively impacts the community. This fact shows conformity with the principles of Islamic legal policy (al-siyasah al-syar’iyyah), prioritizing deliberation, justice, and the common good. However, without a good control function, the autonomy granted to village administrations can open up opportunities for corrupt practices and abuse of authority by village officials.